Cardiac Pathologies Analysis on the Phonocardiogram Signals Using the Bispectral Technic - Debbal Imane, Boudis Hidayat, BAAKEK Yettou Nour El Houda, Debbal Sidi Mohammed El Amine (International Journal of Advanced Science and Technology, 2020)
Cardiac or heart sound carries important diagnosis information of several cardiovascular diseases, such as natural or prosthetic valve dysfunction and heart failure. Hence, algorithms are required for the analysis of cardiac sounds for computer-based automatic diagnosis. In the cardiac sound-based analysis, one of the tasks is to classify abnormal cardiac sounds, i.e. murmurs, caused by various cardiac anomalies. We introduce a new feature named system response, chosen to be estimated using bispectral technique analysis over Fast Fourier bispectrum because of non-stationary and non-Gaussian nature of cardiac sounds. System response feature essentially characterizes the cardiac structure responsible for the production of cardiac sounds, which will be employed later on to automatically classify different types of cardiac murmurs. The cardiac signals analyzed and previously classified will be arranged into three main classes or groups: a group of signals containing neither clicks nor murmurs and having a similar morphology, a second group of signals containing only clicks (reduced murmurs) and a third group containing signals with large murmurs. It has to be noted that all of the heart signals should be part of these three types. The parameters that we are going to define and the graphic representations will help us in this sense to classify the different signals analyzed in one of the mentioned groups.